Patellar tendinopathy outcome predictors in jumping athletes: feasibility of measures for a cohort study. (July 2020) - Tayfur, A.; Salles, J.I.; Miller, S.C.; Screen, H.; Morrissey, D.
Abstract: Objectives: The main aim was to assess feasibility by testing data collection procedures for a cohort study. Measurements validity and reliability were secondary objectives. Design: Feasibility study. Setting: Combination of remote contact, assessment in clinic and biomechanical evaluation. Participants: 36 jumping athletes (female:17, male:19) equally spread between those with patellar tendinopathy, other knee problems and controls. Main outcome measures: Measurements validity, reliability and feasibility. Results: There was no systematic difference between administration methods for patient reported outcome measures and miscellaneous questions (range of d = −0.32 to 0.26) without any order effect (all p > 0.05) except KOOS-PF (p = 0.02). Questionnaires' inter-session reliability was moderate to excellent (ICCs = 0.68–0.93). Pain maps were 94% matched between methods. Training load recall percentage decreased until week-3 with only 20% maintaining a training diary completing the full 6 weeks. The graded loaded challenge was clinically applicable, biomechanically valid with increasing load through progression and reliable (ICCs = 0.63–0.98). Conclusion: The tested questionnaires were valid and reliable for online use, therefore being suitable for clinical and research purposes. A shorter survey to reduce burden and collecting training load using shorter recall duration should improve feasibility. Biomechanical measures were valid and reliable, and a graded loaded challenge, suitable for further testing, has been defined. Highlights: Online use of a PROM questionnaire battery was similar to traditional administration. Collecting training load with shorter recall duration should improve accuracy and feasibility. The graded loaded challenge is suitable for further clinical testing.